Buried refractive microlenses formed by selective oxidation of AlGaAs - Warren, M. E., author; Hou, H. Q., author; Lear, Kevin L., author; Blum, O., author; IEE, publisher (Colorado State University. Libraries, 1996)
The authors demonstrate a novel method of fabricating buried refractive microlenses formed by selective oxidation of AlGaAs epitaxial layers on a GaAs substrate. By appropriate tailoring of the Al mole fraction in the vertical direction, a lens-shaped oxidation shape was achieved. Performance of the microlenses formed in this way was experimentally evaluated at 980nm, and modelled theoretically.
Keywords: oxidation; aluminium gallium arsenide